2012
DOI: 10.1371/journal.pone.0039667
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Antagonistic Probiotic Combination Protecting Ornate Spiny Lobster (Panulirus ornatus) Larvae against Vibrio owensii Infection

Abstract: Vibrio owensii DY05 is a serious pathogen causing epizootics in the larviculture of ornate spiny lobster Panulirus ornatus . In the present study a multi-tiered probiotic screening strategy was used to identify a probiotic combination capable of protecting P. ornatus larvae (phyllosomas) from experimental V. owensii DY05 infection. From a pool of more than 500 marine bacterial isolates, 91 showed definitive in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…While addition of probionts to Artemia cultures has previously shown to reduce pathogenic Vibrio spp. populations (Verschuere et al ., ; Villamil et al ., ), the present study showed that ecological niche specialization by two probionts likely contributed to their additive protective effect against V. owensii DY05 that was observed in an earlier study (Goulden et al ., ). The Pseudoalteromonas probiont PP107 was localized only on external surfaces of the vector organism ( Artemia ) and phyllosomas, while the Vibrio probiont PP05 was primarily localized in their respective digestive systems.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…While addition of probionts to Artemia cultures has previously shown to reduce pathogenic Vibrio spp. populations (Verschuere et al ., ; Villamil et al ., ), the present study showed that ecological niche specialization by two probionts likely contributed to their additive protective effect against V. owensii DY05 that was observed in an earlier study (Goulden et al ., ). The Pseudoalteromonas probiont PP107 was localized only on external surfaces of the vector organism ( Artemia ) and phyllosomas, while the Vibrio probiont PP05 was primarily localized in their respective digestive systems.…”
Section: Discussionmentioning
confidence: 97%
“…Ambient planktonic pathogen cells in the Artemia cultures were reduced in the presence of probionts compared with pathogen‐only controls, confirming that the probionts can inhibit planktonic growth of V. owensii DY05 (Goulden et al ., ). Our previous study showed that planktonic growth of V. owensii DY05 could be inhibited by either of the probiotic strains; however, PP107 was found to be more efficient at low densities (Goulden et al ., ). In the Artemia gut, the pathogen population was significantly reduced from high‐density bioaccumulations in pathogen‐only controls to isolated cells in Artemia enriched with pathogen and probionts, and spread plating confirmed a reduced pathogen load.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study revealed that L. plantarum has the capacity to inhibit S. parasitica and that it would be possible to design new biocontrol of this pathogen in catfish. Moreover, Goulden et al (2012) evaluated the potential of multi-species probiotic treatment and demonstrated that natural microbial communities associated with wild phyllosomas and zooplankton prey support antagonistic bacteria capable of in vivo suppression of a pathogen causing epizootics in phyllosoma culture systems. Ali et al (2013) isolated probiotic strains from different fermented cheese products, which have been reported to show antifungal activity against the plant pathogens Rhizoctonia solani and Fusarium oxysporum.…”
Section: Antifungalmentioning
confidence: 99%